2012
DOI: 10.1016/j.meegid.2011.12.009
|View full text |Cite
|
Sign up to set email alerts
|

The revised Trypanosoma cruzi subspecific nomenclature: Rationale, epidemiological relevance and research applications

Abstract: The protozoan Trypanosoma cruzi, its mammalian reservoirs, and vectors have existed in nature for millions of years. The human infection, named Chagas disease, is a major public health problem for Latin America. T. cruzi is genetically highly diverse and the understanding of the population structure of this parasite is critical because of the links to transmission cycles and disease. At present, T. cruzi is partitioned into six discrete typing units (DTUs), TcI-TcVI. Here we focus on the current status of taxo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

34
760
2
64

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 771 publications
(894 citation statements)
references
References 147 publications
(234 reference statements)
34
760
2
64
Order By: Relevance
“…Our results showed that using two molecular markers was not sufficient for typing of T. cruzi isolates. These limitations were also observed by other authors 32,[60][61][62][63] . However, the use of three genetic markers with different evolutionary rates was able to ensure the correct typing of T. cruzi isolates.…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations
“…Our results showed that using two molecular markers was not sufficient for typing of T. cruzi isolates. These limitations were also observed by other authors 32,[60][61][62][63] . However, the use of three genetic markers with different evolutionary rates was able to ensure the correct typing of T. cruzi isolates.…”
Section: Discussionsupporting
confidence: 63%
“…Although TcII was identified in most T. cruzi isolates, no correlation with clinical forms was observed using rDNA 24Sα, COII, and SL-IR markers and polymorphisms in microsatellite analysis 32 . TcII has been reported as the primary cause of acute ChD and is the typical genotype detected in patients with cardiac and digestive forms of ChD, confirming the association of this DTU with human infection in Brazil and Argentina 57,63 . TcII has also been detected using the same markers with high homology among different hosts and locations in northeastern semiarid 62 .…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…T cruzi parasites are composed of 6 genetic lineages (discrete typing units TcITcVI) [39]. All of the T cruzi lineages have been observed in congenitally infected infants with the exception of TcIV [40][41][42].…”
Section: Epidemiologymentioning
confidence: 99%